A randomised controlled trial of bag–valve–mask teaching techniques. (27th February 2019) - Strzelecki, Charlotte; Shelton, Cliff L; Cunningham, Jennifer; Dean, Charlotte; Naz‐Thomas, Sameera; Stocking, Katie; Dobson, Adam
Summary: Background: Bag–valve–mask (BVM) ventilation is a vital skill in the management of the collapsed patient; however, the quality of BVM ventilation is a cause for concern. Modified techniques, designed to be easier for the novice practitioner, offer an opportunity to improve quality. One such modification is the 'LASOO' (Lift, Apply, Slide, Oppose, Observe) approach, which offers theoretical benefits over the traditionally taught 'CE' (finger shapes) technique. We conducted a randomised controlled trial (RCT) to determine whether LASOO was superior to CE in terms of tidal volume, when taught to novices in the skills‐lab setting. We conducted a randomised controlled trial (RCT) to determine whether LASOO was superior to CE in terms of tidal volume, when taught to novices in the skills‐lab setting Methods: A total of 76 undergraduate health care students received a manikin‐based teaching session on LASOO or CE. They then delivered 20 breaths (10 with each hand) to a modified airway manikin. The primary outcome was mean tidal volume; secondary outcomes were the proportion of breaths that achieved 150‐mL and 400‐mL threshold volumes. Subgroup analyses and statistical modelling were conducted for time‐point, hand dominance and hand size. Results: The mean tidal volume was 320 mL for CE and 304 mL for LASOO. The median percentage of attempts that exceeded 150 mL was 85 for CE and 82.5 for LASOO. The median percentage of attempts that exceeded 400 mL was 20 for CE and 20 for LASOO. The differences recorded between the techniques were not statistically significant. There was a small, statistically significant increase in tidal volume across both techniques with time‐point and holding the mask with the non‐dominant hand. Discussion: LASOO is a viable alternative to CE. Educators may opt to teach either or both techniques, allowing students to choose the technique that they prefer.